Molecular Mechanisms of Action of Undenatured Type II Collagen: Experimental and Clinical Evidence - O. A. Gromova; I. Yu. Torshin; A. M. Lila (Современная ревматология, 2022)
In the treatment of joint diseases, including osteoarthritis (OA), the use of standardized extracts of undenatured type II collagen (UDC-II) is promising. It is known that UDC-II is involved in the regulation of innate and adaptive immunity (reduction of autoimmune reactions that stimulate cartilage degradation) and in the reduction of chronic inflammation activity (modulation of cytokines and prostaglandins). The effect of UDC-II on discoidin receptors of chondrocytes helps to prevent structural disorders of the cartilage connective tissue. Experimental and clinical studies have shown that under the influence of standardized UDC-II, there is an increase in the proportion of regulatory CD4+ T cells, a decrease in the levels of pro-inflammatory cytokines, such as interleukin (IL) 1β, IL6, tumor necrosis factor α, CRP, prostaglandins in the blood, as well as matrix metalloproteinase 3 and NF-κB expression in cartilage. The use of UDC-II in OA leads to a significant reduction in pain, an increase in the range of joint motion, an improvement in joint function according to WOMAC and quality of life.